2015
DOI: 10.5296/jmr.v7i2.6938
|View full text |Cite
|
Sign up to set email alerts
|

Cybercrime over Internet Love Scams in Malaysia: A Discussion on the Theoretical Perspectives, Connecting Factors and Keys to the Problem

Abstract: Increasing cybercrime cases related to the Internet has alert the authority bodies of the country to investigate the causes and actions that need to be taken. Malaysia as a developing country that looking towards advancement of ICT usage in various sectors need to take firm and strategic actions to overcome cybercrime particularly love scams that affect the development of wise generation and degradation of economic growth. There is also a need to take further look into this matter from the ethical point of vie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 5 publications
(4 reference statements)
0
10
0
Order By: Relevance
“…Whitty (2018) found that 60% of women have more historical evidence of romance scams than men, most of whom are middle-aged and welleducated. Unlike Hamsi et al (2015), the victims' weaknesses and the ICT application advancement are the causes that expose the victims to cybercrimes.…”
Section: Problem Statementmentioning
confidence: 99%
See 3 more Smart Citations
“…Whitty (2018) found that 60% of women have more historical evidence of romance scams than men, most of whom are middle-aged and welleducated. Unlike Hamsi et al (2015), the victims' weaknesses and the ICT application advancement are the causes that expose the victims to cybercrimes.…”
Section: Problem Statementmentioning
confidence: 99%
“…The man told the victim that he wanted to give her RM650,000 after one month of online friendship. According to Hamsi et al (2015), these love scam cases explain that scammers set up fake identities at online dating and social networking sites, then make contact and develop an intimate online relationship with the victims. After some time, they create a situation in the urgent need of money, and the victims make several transactions.…”
Section: Scammers' Modus Operandimentioning
confidence: 99%
See 2 more Smart Citations
“…Then [9] also conducted a study entitled "Cybercrime over Internet Love Scams in Malaysia: A Discussion on the Theoretical Perspectives, Connecting Factors and Keys to the Problem". His research concluded that the action of love scammers not only violates the law but also violates morals.…”
Section: Literatur Reviewmentioning
confidence: 99%